Imigração internacional e estratificação no mercado de trabalho brasileiro - Elaine Meire Vilela (2008)
This study seeks to primarily answer the following questions: a) when compared to Brazilians, are international immigrants in worse occupational situations? It should be noted that this study is considering worse occupational situations as unstable professions with poor working conditions and lower salaries; b) Until what point are the variables human capital, cultural capital and social capital important in defining the position of the international immigrants and their salaries in the Brazilian labor market? In order to answer these questions, the study proposes to analyze the insertion of Argentineans, Bolivians, Chileans, Paraguayans, Peruvians, Uruguayans, Chinese and Koreans, compared to non-migrant and migrant Brazilians in the Brazilian labor force. The data used to produce this analysis are based on a sub-sample of the Demographic Census of 2000 (IBGE). The statistical techniques of this study rely upon analyses of logistical, Heckman, and OLS regressions. What one observes is that compared to Brazilians, especially non-migrant Brazilians, the international immigrants have superior occupational status and higher salaries per month. In addition, one can affirm that the origin of the international immigrants positively affects ones insertion, location, and salary within the Brazilian labor market. Now, when compared to the Brazilians migrants, the Uruguayans, the Bolivians, and the Paraguayans earn less for month given that the origin/nationality of these immigrants negatively affects their monthly salaries in the Brazilian labor market. When considering the determining factors related to status, salaries, and the location in the labor market, one observes that the variables of human capital do not have expected effects. The only variable that presents positive statistical significance regarding all the groups analyzed is education. Interestingly enough, experience in the labor market has the opposite effect,which is negative. The proxy variables of cultural capital and social capital do not present regularities in the effect and direction (be it positive or negative) for the groups analyzed.